2013
DOI: 10.1097/brs.0b013e318269c100
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient and Surgeon Preoperative Expectations of Spinal Surgery

Abstract: The findings demonstrate wide discrepancies between the patient and the surgeon regarding the expected result of surgery. They highlight the need for clearer explanations of the association between the spinal problem and neurological deficits and the improvement that can be expected in pain and function after surgery. Systematic, routine evaluation of outcomes should assist in deriving the information necessary to document the improvement achieved and to formulate realistic expectations of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…8,13 Patient expectations have been studied for lumbar stenosis. 9,10,21 Lutz et al reported that patients with better expectations from their surgery had better outcomes after discectomy for disc herniation. 11 In contrast, McGregor and colleagues reported that patients undergoing spinal stenosis surgery frequently had unrealistically high expectations from their surgery and tended to have lower levels of satisfaction; 14,15 similarly, Toyone et al reported that patients with spinal stenosis tend to have more unrealistic and, consequently, unfulfilled expectations.…”
mentioning
confidence: 99%
“…8,13 Patient expectations have been studied for lumbar stenosis. 9,10,21 Lutz et al reported that patients with better expectations from their surgery had better outcomes after discectomy for disc herniation. 11 In contrast, McGregor and colleagues reported that patients undergoing spinal stenosis surgery frequently had unrealistically high expectations from their surgery and tended to have lower levels of satisfaction; 14,15 similarly, Toyone et al reported that patients with spinal stenosis tend to have more unrealistic and, consequently, unfulfilled expectations.…”
mentioning
confidence: 99%
“…The methodological characteristics of the articles found are similar, with 16 observational studies (9)(10)(13)(14)(18)(19)(20)(21)(22)24,26,(30)(31)(32)(33)(34) ; six prospective cohorts (25,(27)(28)34,(36)(37) ; one retrospective cohort (38) , one quasi-experimental study (35) , and one experimental study (29) . The use of instruments occurred in the immediate preoperative period in 21 studies that assessed patients' expectations (10,14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32)(33) , whereas in two studies it occurred when the patient received the indication of surgical treatment (9,27) , one study used them in the intermediate preoperative period (13) ; finally, one study completed the instrument after the patient underwent a spine surgery (34) . Three catego...…”
Section: Resultsmentioning
confidence: 75%
“…The studies were published between 1998 and 2015 and, in general, publications on this subject increased in the last five years (9)(10)14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . The methodological characteristics of the articles found are similar, with 16 observational studies (9)(10)(13)(14)(18)(19)(20)(21)(22)24,26,(30)(31)(32)(33)(34) ; six prospective cohorts (25,(27)(28)34,(36)(37) ; one retrospective cohort (38) , one quasi-experimental study (35) , and one experimental study (29) . The use of instruments occurred in the immediate preoperative period in 21 studies that assessed patients' expectations (10,14,(18)(19)(20)(21)(22)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations